Advantages and disadvantages of biodiesels - Ulusik, Ahmet (SILA SCIENCE, 2011)
In 2000, biodiesel became the only alternative engine fuel in the petroleum poor countries. The biodiesel industry has contributed significantly to the domestic economy. Sustainable energy supply is necessary for the economic development of a country. The direct use of vegetable oils in fuel engines is problematic. Vegetable oils can be used as fuel for combustion engines, but its viscosity is much higher than usual diesel fuel and requires modifications of the engines. The viscosity and other specific properties of biodiesel are close to diesel fuels. There are many benefits the environment, economy and consumers in using biodiesels. The benefits include greenhouse gas reductions including reduced carbon dioxide emissions, which will contribute to domestic and international targets, the diversification of the fuel sector, biodegradability, sustainability, and an additional market for agricultural products.
Keywords: Biodiesel; Advantages; Disadvantages